2015
DOI: 10.1136/vr.103360
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy beyond seizures: a review of the impact of epilepsy and its comorbidities on health‐related quality of life in dogs

Abstract: dog's quality of life (QoL) is of greatest importance to them above their seizure frequency; however, 5 much of the research into canine IE to date has focussed on seizure frequency, and how to reduce it 6 via anti-epileptic drug treatment. In humans, the impact of epilepsy upon QoL has been widely studied, 7 exploring its impact on physical health, but also the psychological health and cognitive capabilities of 8 affected individuals. This paper reviews the existing literature on canine IE, identifying potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 144 publications
(183 reference statements)
1
88
0
Order By: Relevance
“…Causes including genetic and insult‐triggered brain diseases, peripheral diseases, electrolyte imbalances, intoxications and idiopathic . Seizure activity can have substantial impact on quality of life as well as causing emotional distress for owners . To date, most studies have focused on the subset of cases that are classified as epileptic …”
Section: Introductionmentioning
confidence: 99%
“…Causes including genetic and insult‐triggered brain diseases, peripheral diseases, electrolyte imbalances, intoxications and idiopathic . Seizure activity can have substantial impact on quality of life as well as causing emotional distress for owners . To date, most studies have focused on the subset of cases that are classified as epileptic …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IE within the UK dog population is reported at 0.62 per cent (Kearsley-Fleet and others 2013), and raw data from the Royal Veterinary Colleges (RVCs) VetCompass records found that seizures are the third most reported nervous system presentation in dogs (VetCompass 2016). While prevalence alone indicates the importance of this disease, IE also has potentially large welfare implications for the affected dog (Packer and Volk 2015) and can be distressing for owners to witness and manage (Lord and Podell 1999, Wessmann and others 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Understanding whether using imepitoin in polytherapy with other AEDs leads to significant improvements in seizure frequency is of importance, as greater side effects were present in polytherapy patients in this study. Managing the balance of seizure control vs. the impact of side effects remains a challenge in the optimisation of quality of life in epilepsy patients [4, 51]. Exploring alternative management options, including dietary therapy, may be of benefit in the management of seizure activity and anxiety in dogs experiencing adverse effects of polytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that epilepsy is not simply a seizure disorder, with the prevalence of psychiatric disorders in people with epilepsy higher than in either the general population or patients with other chronic medical diseases [14]. The most common co-morbid psychiatric disorders of epilepsy in people are anxiety and depression [2, 58].…”
Section: Introductionmentioning
confidence: 99%